PENGARUH PEMBERIAN TABLET FE + JUS AVOKAD (Persea Americana Mill) TERHADAP KADAR HEMOGLOBIN IBU HAMIL TRIMESTER II DI PMB SURYANI KECAMATAN MEDAN JOHOR TAHUN 2019 - Tri Putri Ageng Utami (COLOSTRUM : Jurnal Kebidanan, 2020)
Introduction: Anemia is a biggest health in the world. According to WHO the prevalence of anemia in pregnant women was 41,8%. Based on the results of Riskesdas that the proportion of anemia in pregnant women in 2013 was 37,1% and in 2018 of 48,9%. To prevent anemia, pregnant women are expected to get at least 90 iron tablets during pregnancy and consume iron-rich foods. Avocados have the nutrients of vitamin C, vitamin E, vitamin K, iron, folic acid, potassium, calories and fat. Iron in avocados is useful for the formation of red blood cells, preventing and treating anemia. Vitamin C helps to absorb iron and calcium Methods: This study aims to determine the effect of Fe + avocado juice (Persea Americana Mill) to haemoglobin levels of second trimester pregnant women in Suryani independent clinic of Medan Johor sub district in 2019. This type of research was Quasi Experiment with Pre Test and Post Test With Control Group Design. The population of this research was all 42 pregnant women with 30 purposive sampling techniques. Results and Discussion: Based on the collection and analysis of data with an average result of haemoglobin in second trimester pregnant women increased by 0,87 gr/dl in the intervention group and 0,8 gr/dl in the control group. There are significant differences between before and after treartment in the intervention group and the control group. In the intervention group and the control group before the treatment there can be no difference which means the data is homogeneous and after the treatment there can be no significant difference which means that Ho is accepted and Ha is rejected. Conclusion: Pregnant women who have Hb levels below normal may be given Fe tablets alone or can be combined to consume avocado juice.